Approximation of analytic functions by generalized shifts of the Lerch zeta-function - Aidas Balčiūnas; Toma Mikalauskaitė; Darius Šiaučiūnas (Mathematical Modelling and Analysis)
In the paper, we approximate analytic functions by generalized shifts of the Lerch zeta-function, where g is a certain increasing to real function having a monotonic derivative. We prove that, for arbitrary parameters λ and α, there exists a closed set  of analytic functions defined in the strip 1/2 < σ < 1 which functions are approximated by the above shifts. If the set of logarithms is linearly independent over the field of rational numbers, then the set  coincides with the set of all analytic functions in that strip.